PENGARUH LATIHAN KNEE TUCK JUMP DAN LATIHAN HALF SQUAT JUMP TERHADAP KEMAMPUAN SMASH KEDENG DALAM PERMAINAN SEPAKTAKRAW - Heriansyah, Heriansyah; Suhartiwi, Suhartiwi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This study aims to determine the extent of the difference in effect between knee tuck jump and half squat jump training on the ability to smash kedeng in sepaktakraw games. By using the field experiment method. The population used is male students of Southeast Sulawesi SMANKO with a sample of 60 people taken by Proposive random sampling. The data analysis technique used is the t-test at 95% significance level. The results showed that; (1) There is a significant effect of knee tuck jump training on the ability to smash kedeng in sepaktakraw games on Southeast Sulawesi SMANKO students, proven to = 13,446> tt = 2,045. There is a significant effect of half squat jump training on the ability of the Kedeng smash in sepaktakraw games on Southeast Sulawesi SMANKO students, proven to = 10.478> tt = 2.045. There is a significant difference in effect between training on the ability to smash kedeng in sepaktakraw games on Southeast Sulawesi SMANKO students, proven, to = 9,970> tt = 2,000.